Mechanisms of natural extracts of Andrographis paniculata that target lipid-dependent cancer pathways: A view from the signaling pathway - Ruth Naomi; Hasnah Bahari; Ong, Zhi Yi; Keong, Yong Yoke; Hashim Embong; Retnagowri Rajandram; Teoh, Soo Huat; Fezah Othman; Rosnani Hasham; Yin, Khoo Boon; Priyatharisni Kaniappan; Muhammad Dain Yazid; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Andrographis paniculata is a local medicinal plant that is widely cultivated in Malaysia. It is comprised of numerous bioactive compounds that can be isolated using water, ethanol or methanol. Among these compounds, andrographolide has been found to be the major compound and it exhibits varieties of pharmacological activities, including anti-cancer properties, particularly in the lipid-dependent cancer pathway. Lipids act as crucial membrane-building elements, fuel for energy demanding activities, signaling molecules, and regulators of several cellular functions. Studies have shown that alterations in lipid composition assist cancer cells in changing microenvironments. Thus, compounds that target the lipid pathway might serve as potential anti-cancer therapeutic agents. The purpose of this review is to provide an overview of the medicinal chemistry and pharmacology of A. paniculata and its active compounds in terms of anti-cancer activity, primary mechanism of action, and cellular targets, particularly in the lipid-dependent cancer pathway.